2018
DOI: 10.1002/mma.4851
|View full text |Cite
|
Sign up to set email alerts
|

Applications of a formula on Beltrami flow

Abstract: In this note, we obtain uniqueness results for Beltrami flow in both bounded and unbounded domain with nonempty boundary by establishing an elementary but useful formula involving operators div and curl. We also use this formula to deal with Maxwell and Stokes eigenvalue problems. KEYWORDSBeltrami flow, Liouville-type theorem, star-shaped domain, the first Maxwell eigenvalue, the first Stokes eigenvalue INTRODUCTIONIn this note, we study the Beltrami flow, that is, a vector field u, which satisfies the systemB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…They play a key role in the proof of the main theorem. The first lemma comes from [17,Lemma 3.2]. In the original version, α ≥ 0 and u ∈ H 1 (D, R 3 ).…”
Section: Proof Of Theorem 11mentioning
confidence: 99%
“…They play a key role in the proof of the main theorem. The first lemma comes from [17,Lemma 3.2]. In the original version, α ≥ 0 and u ∈ H 1 (D, R 3 ).…”
Section: Proof Of Theorem 11mentioning
confidence: 99%
“…Beltrami flows are also called force-free magnetic fields in MHD, since the term (∇ ∧ v) ∧ v models the Lorentz force when v represents the magnetic field, see Moawad (2014) and references therein. By establishing an elementary identity, uniqueness results for Beltrami flow in both bounded and unbounded domains with a non-empty boundary were obtained by Zeng & Zhang (2018). They used that identity to deal with Maxwell and Stokes eigenvalue problems.…”
Section: Three-dimensional Mhd Equilibriamentioning
confidence: 99%
“…Moreover, if the domain is convex, Pauly [12] proved that α 1 = β 1 ≥ µ 2 . For three-dimensional bounded and star-shaped C 1,1 domains, Zeng and the author [16] obtained that α 1 = β 1 < γ 1 . For two-dimensional bounded domains, Kelliher [9] showed that γ k > λ k holds for any positive integer k. For two-dimensional simply connected bounded domains, since the Stokes eigenvalue problem can be rewritten as the clamped buckling plate problem, one can obtain that γ 1 > λ 2 , see [14] or [5].…”
Section: Introductionmentioning
confidence: 99%